Competencies Needed by Agricultural Communication Undergraduates: An Academic Perspective - A. Christian Morgan; K. Jill Rucker (Journal of Applied Communications, 2013)
Communication competencies and skills needed by agricultural communication graduates are constantly changing because of the dynamic nature of the technology used by communication professionals. Although several studies have been conducted in recent years that engaged alumni and industry professionals to determine agricultural communication program graduate competencies, no studies were found which sought out these competencies from the perspective of faculty. Determining the communication competencies faculty deem important will help identify gaps between industry needs and academic perceptions. This Delphi study was conducted to determine the competencies agricultural communication faculty believe are needed for agricultural communication program graduates. Nineteen participants from 14 universities came to consensus on 79 statements. The ten statements receiving the highest level of agreement were “Ability to communicate in writing,” “Ability to write clearly, concisely, tersely, and to get to the point,” “Highly developed writing skills,” “Good writing skills,” “Professional competence - able to practice effective communication - write / speak correctly, clearly in a style and form that is expected of the audience, profession they will serve,” “Critical thinking,” “Grammar,” “Ability to communicate, both orally and in writing, ability to understand conceptual thinking and how it relates to communication,” “Ability to find and use information sources both on and off the internet,” and “Ethics.” This study provides additonal information to help address Agricultural Communications National Research Priority Area 4: “What are the skills, competencies, and resources necessary to prepare professional agricultural communicators for success in various aspects of agricultural knowledge management?”
Keywords: Curriculum; Delphi; undergraduate; faculty; communication